The Reality of Storage and Disposal of Hazardous Medical Waste in Al-Shifa Medical Complex in the Gaza - Alayy, Mohamed Kamel; El-Ashgar, Nizam Mahmoud (Journal of Risk and Crisis Management, 2019)
This research study aims to identify the sources of medical waste in Al-Shifa Medical Complex, the ways of storing it, the disposal mechanisms, the storage places and conditions for the management of medical waste in times of crisis and disaster. The researcher used a descriptive approach to reach the results of the study. The study tool was a personal interview with the employees of Al-Shifa Medical Complex. The study concluded that the classification of hazardous and non-hazardous wastes is not properly carried out, that the temporary collection and storage sites used within the hospital do not conform to WHO specifications. The study concluded also, these wastes constitute a great danger and many problems suffered by the Palestinian society. The study recommended the need to raise the level of cooperation among the concerned authorities in the storage of hazardous medical waste and to establish a special record for each type of medical waste and storage methods.
Keywords: Medical Waste; Hazardous Materials; Crises and Disasters; Palestinian Ministry of Health